Conservative approach to mitral valve replacement in hypertrophic cardiomyopathy with systolic anterior motion – a case report - Suder, Bogdan (Kardiochir Torakochirurgia Pol, 2015)
The authors report the case of a 60-year-old patient with hypertrophic cardiomyopathy (HCM), systolic anterior motion (SAM), and high gradient in the left ventricular outflow tract (LVOT) who underwent surgical treatment. During the surgery, myomectomy of the septum was performed using the Morrow method: despite the persisting SAM and increased LVOT gradients, the mitral valve was not replaced. The case study presents a conservative approach to mitral valve replacement during HCM surgery.